2020
DOI: 10.1371/journal.pone.0228719
|View full text |Cite
|
Sign up to set email alerts
|

Productivity, efficiency, and overall performance comparisons between attendings working solo versus attendings working with residents staffing models in an emergency department: A Large-Scale Retrospective Observational Study

Abstract: Background and objective Attending physician productivity and efficiency can be affected when working simultaneously with Residents. To gain a better understanding of this effect, we aim to compare productivity, efficiency, and overall performance differences among Attendings working solo versus working with Residents in an Emergency Department (ED). Methods Data were extracted from the electronic medical records of all patients seen by ED Attendings and/or Residents during the period July 1, 2014 through June… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

0
6
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 7 publications
(6 citation statements)
references
References 20 publications
0
6
0
Order By: Relevance
“…Taking into account aspects related to working with residents, greater effectiveness was observed in group work than in individual work. ( 38 ). In a study by Kang et al In the United States, emergency departments are constantly under pressure to improve operational efficiency and quality in order to obtain financial benefit and maintain a positive reputation.…”
Section: Discussionmentioning
confidence: 99%
“…Taking into account aspects related to working with residents, greater effectiveness was observed in group work than in individual work. ( 38 ). In a study by Kang et al In the United States, emergency departments are constantly under pressure to improve operational efficiency and quality in order to obtain financial benefit and maintain a positive reputation.…”
Section: Discussionmentioning
confidence: 99%
“…Working alone and working with residents are 2 strategies used by attending physicians in teaching hospitals and the literature reflects mixed results regarding efficiency and productivity for these strategies. 52,53 Using the SEIPS framework, several factors can be identified that influence attending physician documentation: resident completion, patient acuity, EMR usability and functionality, and physical layout. 54 This study also identified strategies used by attending physicians to complete documentation: multitasking, documenting in different locations, and dictation.…”
Section: Discussionmentioning
confidence: 99%
“… 15 , 24 , 25 In emergency department settings, residents have been associated with some positive and negative impacts: increased attending productivity (number of patients seen), decreased efficiency (time to see patients), as well as greater adeptness using the EHR. 26 , 27 Yet to our knowledge, no studies have examined how these contributions interplay directly with attending EHR use.…”
Section: Introductionmentioning
confidence: 99%